The Application of Civil Forfeiture as a Restorative Mechanism in Returning State Financial Losses due to Corruption Crime - Rismawati Nur; Alfin Dwi Novemyanto; Muhammad Rosyid Ridlo (Jurnal Kebijakan Publik, 2025)
Corruption crimes not only result in massive state financial losses but also create inequality of justice and weaken the effectiveness of the legal system. The recovery of state losses has so far relied on a criminal approach that is repressive and limited to court decisions, so that it is unable to reach conditions when the perpetrator escapes, dies, or cannot be brought to trial. This article examines the application of civil forfeiture as a restorative mechanism oriented towards direct asset recovery without requiring proof of criminal guilt. Through a normative juridical research method with statutory, conceptual, and comparative legal approaches, this research analyzes the practice of non-conviction-based asset forfeiture in civil law countries such as France as well as common law countries such as the United States and the United Kingdom. The results of the analysis show that the civil forfeiture mechanism is in line with the principles of restorative justice and can be applied in Indonesia through regulatory reforms that guarantee legal certainty and protection of human rights. The application of an in rem- based asset forfeiture scheme with limited reversal of the burden of proof is considered capable of accelerating the return of state losses while strengthening the eradication of corruption in a sustainable manner.